The Influence of Financial Performance and ESG on Firm Value with Firm Size as Moderator - Ika Nur Avinda; Agus Maolana Hidayat; Budi Rustandi Kartawinata (AIBPM Publisher, 2025)
Firm value illustrates how investors and the market view the company's ability to effectively manage its resources effectively. There are several factors that influence firm value, including financial performance, ESG, and firm size. This research aims to assess the impact of financial performance, ESG, and firm size on firm value, along with the role of firm size in influencing the relationship between financial performance and ESG on firm value. The analytical approach employed in this research is moderated regression analysis (MRA). The sample for this research includes firms engaged in the coal sector that are listed on the Indonesian Stock Exchange (IDX) from 2021 to 2023. Based on purposive sampling, 16 companies were selected. The results of the research indicate that there is a significant partial influence of financial performance, as measured by ROA, CR, and DER, on firm value. ESG disclosure also significantly influences firm value, and firm size also significantly influences firm value. Additionally, firm size, which is also used as a moderating variable, moderates the relationship between liquidity and firm value, as well as leverage and firm value. Through simultaneous testing, the independent variables and interaction variables significantly influence firm value.